Productivity improvement in packaging process throught weight position ranking method in PT.XYZ - Hamidah, Nur (International Journal Multidisciplinary (IJMI), 2024)
XYZ is a food processing company. One of the snacks made is biscuits. The observation process was carried out at PT. XYZ in the biscuit production packaging process. The problem that arises in the packaging process is lead time. This observation aims to make the path more effective in an effort to increase productivity in the packaging process. Track balance is an effort to minimize imbalance between machine to machine or person to person to get the same time at each station. In this observation, the Ranked Position Weihgt (RPW) method was used to determine the workload allocation for each operator. The data analyzed is lead time which is processed to determine the results of track efficiency, balance delay at each work station. This method prioritizes the longest work element time and will be prioritized first to be placed in another work station that represents the lowest work element. Analysis results using the Ranked Position Weight Method with line efficiency 5.52%, Balance Delay 7.71%, Idle time 4.6%..